Faktor yang Mempengaruhi Perkembangan Peserta Didik Anak Sekolah Dasar - Siregar, Ayu Fitria; Hutasuhut, Nayla Audiva; Sitorus, Putri Aulia; Wibowo, Salsabila Putri; Azzahra, Shadrina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The development of students in elementary school is influenced by various interacting factors, such as family factors, social environment, and educational approaches. This research aims to analyze the factors that influence children’s development in physical, intellectual, emotional, social and moral aspects, and the implications for education at the elementary school level. Using descriptive qualitative methods, data was obtained through interviews and observations of students and teachers in an elementary school. The research results show that children’s development in elementary school is greatly influenced by the support of the family environment, peer interaction, and teaching methods at school. This study suggests that educators pay attention to these various factors to support optimal student development.